2000
DOI: 10.1021/ie000151a
|View full text |Cite
|
Sign up to set email alerts
|

Micronization by Rapid Expansion of Supercritical Solutions to Enhance the Dissolution Rates of Poorly Water-Soluble Pharmaceuticals

Abstract: The dissolution of a drug into the biological environment can be enhanced by reducing the particle size of the drug. In this study the rapid expansion of supercritical solutions (RESS) process was employed to micronize racemic ibuprofen, and the dissolution rate of the micronized product in a buffered solution was examined. The chiral nonsteroidal antiinflammatory, racemic ibuprofen, was used as a model drug because its dissolution rate is limited by its poor solubility in water. The phase behavior of the ibup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(141 citation statements)
references
References 16 publications
6
133
1
1
Order By: Relevance
“…For the purpose of micronization, some active pharmaceutical ingredients, such as salicylic acid, 7,8) griseofulvin, 9) ibuprofen, 9,10) have been used. The mean particle size of the drugs obtained by the RESS technique drastically reduced to micron order.…”
mentioning
confidence: 99%
“…For the purpose of micronization, some active pharmaceutical ingredients, such as salicylic acid, 7,8) griseofulvin, 9) ibuprofen, 9,10) have been used. The mean particle size of the drugs obtained by the RESS technique drastically reduced to micron order.…”
mentioning
confidence: 99%
“…Although the SEM images showed that the particles were aggregated, they were easily dis- persed upon ultrasonification in water as confirmed by the results of particle size distribution measured by Malvern Mastersizer. 7 Process parameters such as temperature, pressure, and nozzle design did not significantly influence the ibuprofen precipitate characteristics. The composition of enantiomer in racemic ibuprofen was 1:1 and did not change while processed by the RESS technique.…”
Section: Micronization Of Ibuprofen By Ress Processmentioning
confidence: 90%
“…The details of the experimental technique have been described previously. 7 ASES: The schematic diagram of the ASES apparatus is presented in Figure 2. Micronization by the ASES process was conducted by first pressurizing the precipitation vessel to the desired pressure and then allowing the CO 2 to flow through the vessel from the top.…”
Section: Ressmentioning
confidence: 99%
“…Moreover, in previous studies about the variation of solubility of the ibuprofen versus time [29] , it is demonstrated that its solubility increases exponentially in the time. Due to the hydrophobic nature of ibuprofen, the aggregation of ibuprofen powders is obtained during the dissolution testing [29]. And, in this study, there is a good dispersion of the ibuprofen, because, basically, this takes part of a microencapsulation system, thus avoiding the aggregation of the active agent.…”
Section: Viable Skin (Epidermis-dermis)mentioning
confidence: 96%
“…According to the literature [26,[28][29][30], the solubility of ibuprofen in a phosphate buffer solution (receptor fluid) at a temperature of 37 °C and pH = 7.4 is 6.02 mg/mL. However, ibuprofen has a very low water solubility (0.14 mg/mL), and in the lipophylic layer (SC) the ibuprofen release is slower than in the hydrophilic domain (epidermis-dermis).…”
Section: Viable Skin (Epidermis-dermis)mentioning
confidence: 99%